A.P. CHEKHOV IN THE ARTISTIC RECEPTION OF E. BLAZHEEVSKY (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-1-32-39The various facets of the reception of the Chekhov tradition are analyzed in the work of E. Blazheevsky, a Russian poet of the second half of the 20th century. There was revealed the similarity of motives and images with Chekhov's story “Studentˮ and the common features of the structure of the poetic and prose text were determined. While analyzing Blazheevsky's poem “The Lady with the Dogˮ, it was found that the work of the poet of the 20th century is based on the transformation of the plot and images of Chekhov's story, on a direct dialogue with the work of the classic writer. Thus, the various ways of reception of the Chekhov tradition in the poetry of E. Blazheevsky have been analyzed.Key words: lyrics, Evgeny Blazheevsky, Anton Chekhov, traditions, motifs, images